Non-Verbal Communication in Greetings in Chinese: a Pedagogical Proposal (Sinología hispánica. China Studies Review, 2019)
Due to the problems detected in the practice of teaching Chinese as second Language, on the other hand with the theoretical advances both in nonverbal communication and in pedagogy, especially in that of Chinese language, we began to reflect on the importance of the nonverbal language in intercultural communications. It is found that it necessary to make a theoretical and practical proposal for the integration of nonverbal communication into the Chinese language teaching materials, for the purposeof improving our students’ communication andthe comprehension on the culture and societyof China. In this goal, the present work consistsin the analysis of nonverbal signs used in somespecific communicative contexts in Chineserelated to the topic of “greetings”, and in theidentification of those nonverbal signs that canmore easily cause errors of interpretation in thestudents, mainly by questionnaire, interviews andbibliographic review. Finally, based on the resultsof our study, we present a concrete pedagogicalproposal composed by five activities, in orderto offer a complementary material that couldhelp the students to avoid misinterpretations inspoken or written context that block and distortthe transmission of messages.